Changes in Estonian organizations from institutional perspective - Alas, Ruth (Journal of Business Economics and Management, 2004)
During last decade Estonia has passed through its transition from the authoritarian, centralized, totalitarianism of state socialism, to the democratic country with a free market economy, with different attitudes and values. Estonian companies have been in continuous change process and remarcable part of these changes are deepest by scope ‐ transformational changes. Author proposes that the social phenomena such as organizational change can only be understood in relations to the wider contextual influences that surround them. Changes in Estonian companies could be explained by using institutional and historical context. Research in Estonian companies indicates, that during stable institutions developmental or transitional changes take place in organizations, during societal transience transformational changes occur in organizations.First Published Online: 14 Oct 2010